The Involvement Of Austin's Ideas In Semantics - Ahmadin, Dimjati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
There are instructions from the theory of speech acts that in the initial period, there were differences of opinion among experts. Philosophy, just like the difference between Ibnu Sina and Thomas Hobbes, the first time to examine the problem firmly and complete namely research conducted by J.L. Austin (linguist). This library research intends to study whether two prominent writers in the field semantics namely John Lyons in his book